Laparoscopic continuous seromuscular circumsuture for myomectomy: a real-world, retrospective, East-Asian cohort study - Han Wu; Jianhua Zhu; Xueqin Shi; Jinmei Liu; Linyan Zhang (BMJ Open)
Objective This study aimed to introduce a novel laparoscopic haemostasis for myomectomy and investigate the independent risk factors for uterine fibroid recurrence.Design A retrospective cohort study.Setting Following strengthening the reporting of observational studies in epidemiology (STROBE) criteria, a retrospective study of prospectively collected available data of the consecutive patients who underwent the myomectomy in the department of obstetrics and gynaecology of the single centre between February 2018 and December 2020.Participants 177 patients who underwent laparoscopic myomectomy resection were enrolled in the present cohort study.Materials and methods Patients were classified into two groups according to their different methods of haemostasis in laparoscopic surgery. Recurrence-free survival was compared between the groups during an average follow-up of nearly 2 years.Results Of the 177 patients from 672 consecutive patients in the retrospective cohort, laparoscopic circular suture and baseball suture were carried out in 102 (57.6%) and 75 (42.4%) patients, respectively. The total amount of blood lost during surgery varied significantly (37.6 vs 99.5 mL) (p<0.001). Univariable analyses identified that age ≥40 years, position at intramural myoma, multiple fibroids and largest fibroid volume ≥50 mm3 (HR 2.222, 95% CI 1.376 to 3.977, p=0.039; HR 3.625, 95% CI 1.526 to 6.985, p=0.003; HR 3.139, 95% CI 1.651 to 5.968, p<0.001; HR 2.328, 95% CI 0.869 to 3.244, p=0.040, respectively) are independent risk factor of the recurrence of uterine fibroids. The formula of the nomogram prediction model was established as the practical clinical tool.Conclusion The laparoscopic continuous seromuscular circumsuture for myomectomy can effectively reduce the amount of surgical bleeding and accelerate the perioperative recovery for surgical safety. The main factors affecting the recurrence of uterine fibroids were age, location, number and volume of uterine fibroids. The nomogram can more straightforwardly assist clinicians to determine the risk of recurrence after laparoscopic myomectomy.